TREND DAN DETERMINAN KEY AUDIT MATTERS (ISA 701): STUDI LITERATUR TAHUN 2016-2025 - Wulan, Diajeng Fitri (Jurnal Riset Terapan Akuntansi, 2025)
This study examines the trends, determinants, and impact of Key Audit Matters (KAM) disclosures based on International Standard on Auditing (ISA) 701 from 2016 to 2025. Utilizing a Systematic Literature Review (SLR) with the PRISMA framework methodology, 73 Scopus indexed articles were analyzed. The findings reveal a shift in trends from descriptive identification of KAMs to evaluating their impact and effectiveness, including effects on audit quality and investor perceptions. The most frequently disclosed KAM topics are goodwill impairment and fair value measurements, while Environmental, Social, and Governance (ESG) issues are rarely integrated. KAM disclosures enhance financial reporting transparency and management accountability, despite challenges such as the use of boilerplate language and auditor inconsistencies. Significant differences in KAM practices were found between emerging countries (fewer and generic) and developed countries (more detailed and systematic). Keywords: Key Audit Matters, ISA 701, Audit Quality, Literature Review